Investigating Sport Stakeholders' Understanding of Behaviour Management within a Competitive Youth Baseball Team - Joseph John Gurgis; Gretchen Kerr; Anthony Battaglia (MDPI AG, 2023)
The following study employed an instrumental case study to investigate sport stakeholders' understandings of behavioural management strategies used in competitive youth baseball, including the identification of common strategies and interpretations of these as punishment or discipline. Twenty-one participants, from one competitive (AAA) all-boys baseball team, including three coaches, eleven baseball players, and seven parents, were recruited to participate in an individual semi-structured interview. Interviews ranged between 30 and 150 min, and data were analyzed using reflexive thematic analysis. Several behaviour management tactics were identified, of which exercise, benching and yelling negative comments were most often reported. While participants interpreted excessive exercise and benching as punitive and/or disciplinary approaches to behavioural management, yelling was consistently viewed as punitive. Participants confused punishment and discipline as interchangeable, thus suggesting a lack of awareness regarding developmentally appropriate strategies of behavioural management and highlighting the normalization of certain punitive tactics in youth sport. The results underscore the necessity of imparting knowledge to the sports community regarding age-appropriate behavioural management interventions to foster safe and enjoyable athletic experiences for youth competitors.